Analisis Penjadwalan Pekerjaan Tanah (Land Clearing) Pada Proyek Perumahan Bunda Asri Menggunakan Precedence Diagram Method - Rendy Yulianto Ramadhani (Konstruksi: Publikasi Ilmu Teknik, Perencanaan Tata Ruang dan Teknik Sipil, 2023)
The Bunda Jombang Housing development project is a project that has a land area of ​​31,401 hectares, where this housing development project was previously located on a former quarry land (Andim Rendy S, 2022), therefore it is necessary to carry out land work (land clearing) to restore the existing land structure. damaged as a result of previous mining activities. Researchers schedule earthworks so that there are no deviations from the planned schedule. An appropriate scheduling method is needed for efficient and effective utilization of the resources used. Research using the Precedence Diagram Method has the aim of analyzing implementation time and being able to determine effective scheduling for continuous work in housing development projects. (Author, 2021)